Opportunity, job pressure and deviant workplace behaviour: Does neutralisation mediate the relationship? A study of faculty members in public universities in Nigeria - Michael Olalekan Adeoti; Faridahwati Mohd Shamsudin; AlHamwan Mousa Mohammad (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The purpose of the present study was twofold: (1) to examine the direct effect of the dimensions of opportunity (i.e. ethical climate and institutional policy) and dimensions of job pressure (i.e. workload and work pressure) on workplace deviance (i.e. organisational and interpersonal deviance) and (2) to assess the mediation of neutralisation in the relationship between the dimensions of opportunity, job pressure and workplace deviance. Design/methodology/approach - The present study drew from the fraud triangle theory (FTT; Cressey, 1950) and the theory of neutralisation (Sykes and Matza, 1957) to achieve the research objectives. Survey data from 356 full-time faculty members in Nigerian public universities were collected. Partial least square-structural equation modelling (PLS-SEM) was employed to analyse the data. Findings - The results indicated that opportunity and job pressure significantly affected workplace deviance. As expected, neutralisation was found to mediate the negative relationship between ethical climate and interpersonal deviance and the positive relationship between workload, work pressure and interpersonal deviance. Contrary to expectation, neutralisation did not mediate the relationship between opportunity, pressure and organisational deviance. Research limitations/implications - The sample was drawn from academics in public universities and the cross-sectional nature of this study means that the findings have limited generalisations. Practical implications - This study offers insights into the management of Nigerian public universities on the need to curb workplace deviance amongst faculty members. This study recommends that the management improve the work environment by enhancing the ethical climate and institutional policies and reviewing the existing workload that may constitute pressure to the faculty members. Originality/value - The present study provides empirical support for the fraud triangle theory and theory of neutralisation to explain workplace deviance.
Keywords: 650; Job pressure; Neutralisation; Opportunity; Workplace deviance